Public health in 1948 : Remarkable statistics. The first months of the National Health Service
1950-03-31 1950 1950s 8 pages 9,000 patients on the waiting list were a grave danger to their contacts. If all the beds already provided could have been made available for use, more than one-third of these patients could have been brought under institutional treatment and education, and thus isolated from their families. [P. 108] On the 30th June, 1948, 29,420 patients were receiving institutional treatment and 9,210 were on the waiting lists. About 10 per cent of the provided beds were temporarily not available, four-fifths on account of shortage of domestic and nursing staff. Mass Radiography. Some 966,000 civilians were examined by mass miniature radiography during the year, bringing the total number of persons examined in England and Wales up to 31st December, 1948, to 2,985,607 (1,718,155 males and 1,267,452 females). [P. 108] Of the total numbers examined 94.4 per cent. were found at the time to have no abnormal chest condition. Previously unsuspected active tuberculosis of the lungs was revealed in slightly less than 4 per 1,000 (1,279 persons) 2.3 per cent. had inactive or "observation" tuberculosis of the lung. The results did not suggest any association between incidence and work in any of the main occupational groups. An epidemiological study of the disease in industry by Doctors Alice Stewart and J.P.W. Hughes supported this by finding that there is no evidence of a specific industrial hazard in boot and shoe factories (where in fact the death-rate for diseases other than tuberculosis is below average), although they suggest that it may yet be shown that size of working unit is an important factor in determining disease incidence in any occupation. [P. 109] B.C.G. The intention in the first place is not to encourage general inoculation of the public at large but to concentrate on those groups of the population considered to live at a more than average risk of tuberculous infection. [P. 115] PUBLIC HEALTH LABORATORY SERVICE The Public Health Laboratory Service continues to expand and take an ever increasing share in preventive medicine as is shown in various directions such as the great value now attached to Vi-phage typing; the success of a new method in the bacteriological examination of sewage; the greatly increased work done in the investigation of food poisoning outbreaks, and the trials of whooping cough, vaccine and of gamma globulin antibodies for measles prophylaxis. [P.92] THE NATIONAL BLOOD TRANSFUSION SERVICE The rapid increase in the demand for blood continued. Although there were 374,000 donors enrolled some 200,000 more are needed for optimum working. Donor recruitment continued satisfactorily during the year, but more effort is required to enrol new donors, particularly in the London area where the donor panel is considerably below the optimum working size. [P. 103] MENTAL HEALTH Few appreciate the size or importance of the problem of mental illness. At the end of 1948 there were in England and Wales approximately 200,000 beds for mental illness and mental defectives and 315,000 beds for all other types of illness. The total number of mentally disordered and defective patients under care at the end of 1948, was respectively 145,779 and 54,887. At the end of 1948 it was estimated that approximately another 3,000 male and 8,000 female nurses were required. The great advances in the physical treatment of mental disease are described - malarial therapy, therapeutic convulsion treatment, insulin shock treatment and leucotomy - all empirical methods which have opened up new fields of treatment and research. They have given a great impetus to psychiatry. [Pp. 125, 127, 129 and 133] - 5 - 292/847/5/38